The Effect of Thinking Styles on Volleyball Serve Learning in Adolescent Female Students Based on Sternberg’s Model - Aghdasi, Mohammadtaghi; Razi Al Basharat Al Rakabi, Sammer; Fathirezaie, Zahra (Health Nexus, 2025)
The role of thinking styles in learning psycho-motor skills, such as volleyball serve, is rarely investigated in female volleyball players. This study was an attempt to fill this gap. This quasi-experimental study with a pretest-posttest approach aimed at investigating the effect of thinking styles, based on Sternberg’s model, on volleyball serve learning in female adolescent students. To determine the sample size, G*Power v3.1 was used (α = 0.05, power = 0.95, and number of parameters = 3), and 45 female students (average age = 16.5, SD = 0.85) who met the inclusion criteria were selected through convenience sampling from one of secondary schools in Nasiriyah, Iraq. Based on the their thinking styles, after administering the Thinking Style Inventory - Short Version, they were divided into three 15-member groups, i.e., Type I, Type II, and Type III. They took AAHPERD Volleyball Skills Test as the pretest, and as the acquisition, retention and transfer tests. The training program lasted for 12 weeks, 3 sessions per week, and each session for 60 minutes in accordance with the pre-determined protocols and guidelines of AAHPERD test. The data were analyzed using a mixed ANOVA. There was a significant difference in volleyball serve learning between the groups, with Type I outperforming Type III, while no significant difference was detected between Type I and Type II, or between Type II and Type III. In teaching and evaluating psycho-motor skills, enough attention should be paid to thinking styles, as it can help teachers to employ a variety of methods in this regard. The variety and flexibility they create by taking into account the students’ thinking styles determine whether and to what extent they succeed in the teaching process.